Are proton pump inhibitors really so dangerous?. Issue 8 (August 2016) - Savarino, Vincenzo; Dulbecco, Pietro; Savarino, Edoardo
Abstract: For decades, millions of patients with acid-related disorders have had their acid inhibited effectively and safely first with H2-receptor antagonists (H2RAs) and then with proton pump inhibitors (PPI). As with any pharmacological agent, PPIs have been reported to be associated with some adverse events, but several recent large-scale observational studies have evidenced new and serious abnormalities generally linked to their chronic use. However, these studies have often important limitations for their frequent retrospective design and other methodological drawbacks, such as selection biases of the analyzed populations and the presence of various confounding factors. Overall, although the conclusions of these pharmacovigilant investigations must be taken into account and can generate important hypotheses for future research, they do not have to create panic among patients and alarmism among physicians. On considering the weakness of these studies, we suggest physicians should not refrain from continuing to use PPIs, if these drugs are given for medical indications clearly established in the literature and, more importantly, they should not be induced to shift to H2RAs, a class of antisecretory agents that are much less effective than PPIs. A return to the past is potentially dangerous for the patients, taking into account the well-known success of PPIs in the wide spectrum of all acid-related conditions.